UniMóvil: A Mobile Health Clinic Providing Primary Care to the Colonias of the Rio Grande Valley, South Texas - Manusov, Eron G.; Diego, Vincent P.; Smith, Jacob; Garza, Jesús R.; Lowdermilk, John; Blangero, John; Williams-Blangero, Sarah; Fernandez, Francisco (Frontiers in Public Health, 2019)
Background The Rio Grande Valley (RGV) is a region of South Texas is home to over 240,000 people living in areas known as Colonias. A mobile unit (UniMóvil) was used to delivery primary healthcare to the highly medically underserved population residing in the Colonias. A model of care was developed to address access to healthcare. Seven clinical outcomes including obesity, diabetes, hypertension, hypertriglyceridemia, low high density lipoprotein cholesterol (HDL-C) levels, and depression were measured. Health-related quality of life was assessed using the Duke Health Profile. Methods Baseline prevalence, associations, and contributing factors were characterized. Regression analysis and generalized linear/logistic modeling were used to determine potential predictors of clinical variables. The Duke Health Profile and Patient Health Questionnaire (PHQ9) were used to evaluate health related quality of life and depression. Missing data imputation approaches were used to ensure unbiased regression estimates and adequate coverage of the 90% confidence intervals. Results The average age of patients was 45 years old and females represented 67 % of the population served. There was a high prevalence of obesity (55.5 %), hypertension (39%), diabetes (32.5%) and depression (19 %). Self-perceived health status was generally low, and depression predicted all 11 domains of the Duke Health Profile. Conclusion Patients seeking care through a mobile clinic serving the Colonias in South Texas had a high prevalence of diabetes, hypertension, obesity, and depression. The self-perceived health of Colonia residents is low. Data collected indicated an association between depression and diabetes, as well a negative impact of chronic disease on perceived health. There was a difference in perceived quality of life between residents of the two Colonias. Data recorded from care of Colonia residents can be used to further develop and concentrate healthcare delivery to positively affect quality of life in the Colonias of South Texas.